2021
DOI: 10.1111/ocr.12470
|View full text |Cite
|
Sign up to set email alerts
|

Distalization of maxillary molars using temporary skeletal anchorage devices: A systematic review and meta‐analysis

Abstract: Distalization of maxillary dentition is an efficient option, especially for patients seeking non-extraction treatment modalities. 1 Nevertheless, the fundamental quandary is finding the appropriate anchorage that will not produce unwanted side effects. Extraoral anchorage and non-compliance intraoral appliances such as the pendulum and distal jet have been used for maxillary molar distalization. 2,3 However, they often yield undesirable tooth movement such as distal tipping and extrusion of molars and protrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
2
21
0
2
Order By: Relevance
“…3,4 However, these appliances depend on patient compliance and easily result in anchorage loss, which limits their clinical application. 5,6 In recent years, the use of microimplants in orthodontic practice enables better treatment outcomes in molar distalization. 6,7 The success of molar distalization depends on having enough available posterior space.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, these appliances depend on patient compliance and easily result in anchorage loss, which limits their clinical application. 5,6 In recent years, the use of microimplants in orthodontic practice enables better treatment outcomes in molar distalization. 6,7 The success of molar distalization depends on having enough available posterior space.…”
Section: Introductionmentioning
confidence: 99%
“…During retraction of the maxillary arch with TSADs, one of the consistent side effects is reported to be intrusion of the molars with a slight clockwise rotation of the occlusal plane. Most studies showed that the amount of the maxillary first molar intrusion was close to 1 mm or less, except for one case in which 2.9 mm was reported 20 . This phenomenon is related to the fact that the retraction force vector is applied below the center of resistance in the maxilla.…”
Section: Discussionmentioning
confidence: 90%
“…Most studies showed that the amount of the maxillary first molar intrusion was close to 1 mm or less, except for one case in which 2.9 mm was reported. 20 This phenomenon is related to the fact that the retraction force vector is applied below the center of resistance in the maxilla. Conversely, the protraction force vector from the palatal TSADs may cause unwanted extrusion of the molars with a counterclockwise rotation of the occlusal plane.…”
Section: Treatment Resultsmentioning
confidence: 99%
“…3,4 With the introduction of the temporary skeletal anchorage devices (TSADs), buccal miniscrews have been used to correct Class II malocclusion by distalizing maxillary molars. [5][6][7] When a large amount of total arch distalization is needed, interdental miniscrews need to be relocated because of the limited inter-radicular distance. 8 To overcome this drawback, palatal placement of TSADs has been proposed by some clinicians due to the broader range of tooth movement possible and less tipping of the first molars.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of the temporary skeletal anchorage devices (TSADs), buccal miniscrews have been used to correct Class II malocclusion by distalizing maxillary molars 5‐7 . When a large amount of total arch distalization is needed, interdental miniscrews need to be relocated because of the limited inter‐radicular distance 8 .…”
Section: Introductionmentioning
confidence: 99%